Diabetic Care Provision and Glycemic Control in a Pediatrics Diabetic Clinic: An Audit (Medical Forum Monthly, 2024)
Objective: To study the glycemic control and factors associated with glycemic control of children with type 1 diabetes mellitus attending the diabetic clinic of pediatric department of Khyber teaching hospital.Study Design: Retrospective / observational study.Place and Duration of Study: This study was conducted at the Diabetic Clinic of Pediatric Department, Khyber Teaching Hospital, Peshawar from January 2015 till December 2017.Materials and Methods: An audit of all the diagnosed diabeticpatients attending the diabetic clinic for at least one year of pediatric department of Khyber teaching hospital. Every scheduled follow up visit was recorded by a resident doctor on a Performa. The self-monitored blood glucose record, insulin dose, injection site, technique and site rotation were checked. Dietary compliance was checked and 24 hour dietary record taken. Any change in dose needed was planned and a follow-up date was given. All these follow up Performa were studied and data was extracted from them.Results: The number of patients that completed the study were 54(27 males and 27 females). The mean age of patients in this study was 8.5 years. Mean duration of diabetes was 1.89 SD 0.6. The mean HbA1c at the beginning of the study was 10% and at the end of study was 8.5%. The number of patients with good glycemic control were18 and with intermediate were 14 and poor were 22.Conclusion: Good glycemic control was significantly associated with parent being literate, frequent home blood glucose monitoring, regular follow up visits and good dietary compliance.